2016
DOI: 10.1155/2016/1560161
|View full text |Cite
|
Sign up to set email alerts
|

Technical Innovation Case Report: Ultrasound-Guided Prolotherapy Injection for Insertional Achilles Calcific Tendinosis

Abstract: We describe the use of ultrasound guidance for hyperosmolar dextrose (prolotherapy) injection of the distal calcaneal tendon specifically just anterior to identified enthesophytes in patients with insertional Achilles calcific tendinosis refractory to conservative treatment. This specific technique has not to our knowledge been described or used in literature previously.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…The reason for separating out this finding here is to draw attention to the differences in treating calcific tendonopathy compared to non-calcific tendonopathy. Calcifications within the tendon may respond to extracorporeal shock wave therapy, prolotherapy, and surgery [ 123 , 124 , 125 ].…”
Section: Calcific Tendonopathymentioning
confidence: 99%
“…The reason for separating out this finding here is to draw attention to the differences in treating calcific tendonopathy compared to non-calcific tendonopathy. Calcifications within the tendon may respond to extracorporeal shock wave therapy, prolotherapy, and surgery [ 123 , 124 , 125 ].…”
Section: Calcific Tendonopathymentioning
confidence: 99%
“…All of studies reported about good improvement of pain using the VAS score after dextrose prolotherapy treatment. A total of 6 studies reported improvement in supraspinatus tendon tear or pathology [8][9][10][11][12][13], 6 studies reported in Achilles tendon cases [4,[14][15][16][17][18] studies reported improvement in pain VAS score in treatment of patellar tendon, meniscus, acromion enthesopathy, anterior cruciate ligament laxity and anterior tibiofibular ligament injury [19][20][21][22][23].…”
Section: Pain Visual Analog Scale Scorementioning
confidence: 99%
“…Eleven studies reported there were improvement of functional outcome after dextrose prolotherapy [9][10][11][13][14][15]18,19,[21][22][23]. Five studies used a special scoring to evaluate the outcome.…”
Section: Functional Outcomementioning
confidence: 99%
See 2 more Smart Citations